Managing for biodiversity in humid tropical forests - Sayer, Jeffrey A.; Zuidema, Pieter A.; Rijks, M.H. (1995)
One of the major issues surrounding the debate on sustainability of management of tropical forests is the impact of different forest management strategies on biodiversity. Recent research has suggested a number of options for minimising the risks to biodiversity of forestry operations. The maintenance of extensive conventional national parks and equivalent reserves still constitutes the best option from the purely biological standpoint. However, social, economic and demographic realities coupled with increased knowledge of the ecology and distribution of tropical forest species, suggests that appropriate forestry practice can contribute significantly to biodiversity conservation. The optimal strategy should be based upon a system of conventional protected areas, complemented by a reduction of the impact of harvesting and the retention of unlogged refugia in logged-over-forests.